Demonstrating the potential of iron-doped strontium titanate electrolyte with high-performance for low temperature ceramic fuel cells. (August 2022) - Shah, M.A.K. Yousaf; Lu, Yuzheng; Mushtaq, Naveed; Rauf, Sajid; Yousaf, Muhammad; Asghar, Muhammad Imran; Lund, Peter D.; Zhu, Bin
Abstract: Electrolytes with high-proton conduction and low activation energy are attractive for reducing the high operating temperature of solid-oxide fuel cells to less than <600 °C. In this work, we have fabricated semiconducting electrolyte SrFeTiO3-δ (SFT) material exhibiting high ionic conduction and exceptionally high protonic conduction at low operating temperature but with low electronic conduction to evade the short-circuiting issue. The prepared fuel cell device exhibited high open-circuit voltage (OCV) and a high-power output of 534 mW/cm 2, of which 474 mW/cm 2 could be for sure be related to the protonic part. The current study suggests that usage of semiconductor SrFeTiO3-δ facilitates a high concentration of oxygen vacancies on the surface of SFT, which mainly benefits proton conduction. Moreover, lower grain boundary resistance leads to obtain higher performance. Also, the Schottky junction phenomena are proposed to inhibit the e-conduction and excel the ions transportation. The high performance and ionic conductivity suggest that SFT could be a promising electrolyte for protonic ceramic fuel cells. Graphical abstract: Image 1